2015
DOI: 10.1155/2016/1718041
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Promotes Cardiac Differentiation of Human Induced Pluripotent Stem Cells

Abstract: Background. Human induced pluripotent stem cells (iPSCs) are an attractive source of cardiomyocytes for cardiac repair and regeneration. In this study, we aim to determine whether acute electrical stimulation of human iPSCs can promote their differentiation to cardiomyocytes. Methods. Human iPSCs were differentiated to cardiac cells by forming embryoid bodies (EBs) for 5 days. EBs were then subjected to brief electrical stimulation and plated down for 14 days. Results. In iPS(Foreskin)-2 cell line, brief elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 25 publications
2
69
1
Order By: Relevance
“…pacing at the rates below the intrinsic rate is not effective). To account for the dependence of action potential on the beating rate in iPSC-CMS an empirical formula, Bazet (Hernandez et al , 2016; Kim et al , 2010) or Fridericia (Lewis et al , 2015; Maddah et al , 2015) is usually used, that may not accurately correct for the rate dependence in the wide range of beating rates observed after drug treatments. The need for the forced rate correction would be overcome in a more mature and pure ventricular iPSC-CMs that did not demonstrate spontaneous depolarizations.…”
Section: Discussionmentioning
confidence: 99%
“…pacing at the rates below the intrinsic rate is not effective). To account for the dependence of action potential on the beating rate in iPSC-CMS an empirical formula, Bazet (Hernandez et al , 2016; Kim et al , 2010) or Fridericia (Lewis et al , 2015; Maddah et al , 2015) is usually used, that may not accurately correct for the rate dependence in the wide range of beating rates observed after drug treatments. The need for the forced rate correction would be overcome in a more mature and pure ventricular iPSC-CMs that did not demonstrate spontaneous depolarizations.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was suggested that electrical stimulation promotes cardiac differentiation and maturation of hiPSC-derived cardiomyocytes [40][41][42]. Ruan et al [41] reported that electrical stimulation promotes force maturation of induced pluripotent stem cell-derived cardiac tissue; however, the cardiomyocytes used in this study were only 2 or 3 weeks old.…”
Section: Discussionmentioning
confidence: 75%
“…Ruan et al [41] reported that electrical stimulation promotes force maturation of induced pluripotent stem cell-derived cardiac tissue; however, the cardiomyocytes used in this study were only 2 or 3 weeks old. Damián Hernández et al [42] reported that electrical stimulation promoted cardiac differentiation; however, the parameters of electrical stimulation were set at 1 Hz and for a very short period of approximately 15 min. The effects of stimulation when extended to a longer time or on older cardiomyocytes remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…While hiPSC-derived cardiomyocytes hold promise for human-origin and patient specific disease modeling, it has been widely reported that these cells resemble the fetal cardiomyocytes rather than adult ones 33 . It has been shown in other studies that iCMs mature with time 66 and with mechanical 33,67 or electrical 33,67,68 stimuli. Here we show that regardless of the iPSC origin, iCMs mature in vitro with prolonged culture time, and start showing marks of cellular aging at the later culture stages, through 120 days of culture we conducted in this study.…”
Section: Discussionmentioning
confidence: 79%